(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the semantics of conditional means in the Uzbek literary language. The expression of the meaning of the condition in speech (sentence, text) with one, two or three means is explained. Forms denoting the meaning of the condition in a favorable context express the terms of the present, past, and future tenses, clarify or strengthen these terms in a clarifying context, and change the paradigmatic nature of these forms in an unfavorable context. Attention is also paid to the use of the auxiliary word (agar) denoting the condition.